Cleaning of InGaAs and InP Layers for Nanoelectronics and Photonics Contact Technology Applications. (11th September 2015) - Rodriguez, Philippe; Toselli, Laura; Ghegin, Elodie; Rebaud, Mickaël; Rochat, Névine; Chevalier, Nicolas; Martinez, Eugénie; Nemouchi, Fabrice
Abstract : InGaAs and InP layers were treated by using Ar and He direct plasmas coupled with wet chemical treatments. InP surfaces are more sensitive to the various treatments than the InGaAs ones. Suitable and efficient treatments have been proposed to offer a good compromise between impact on surface and native oxide removal. We have demonstrated that concentrated HCl solution cleanings followed by He direct plasma treatment are efficient for the removal of InGaAs native oxides whereas He plasma exposure combined to a diluted HCl solution cleaning is more suitable for InP surfaces.